The association between pregnancy outcomes of frozen thawed embryo transfers and previous SARS-CoV-2 infections - Hao Zhao; Fen Tian; Shaodi Zhang; Saijiao Li; Ning Li; Jing Zhang; Zenghui Mao; Qianjie Zhang; Rong Li; Ying Liang; Cuilian Zhang; Yanping Li; et al. (Scientific Reports)
Abstract The present study aimed to explore whether there is an association between the transfer of frozen thawed embryos (FET) obtained during SARS-CoV-2 infection and an increased risk of adverse pregnancy outcomes. We performed a case-control cohort study. Couples undergoing FET treatment in six reproductive centers in four provinces from February 2022 to December 2022 were enrolled. A total of 440 couples who underwent FET treatment participated in this study, with 110 and 330 couples in the SARS-CoV-2 -positive and SARS-CoV-2-negative cohorts, respectively. The baseline characteristics of the cohorts were comparable. The SARS-CoV-2-positive cohort had statistically significantly lower ongoing pregnancy rate, clinical pregnancy rate, implantation rate, and live birth rate than that of the SARS-CoV-2 -negative cohort. Analysis of the effects of previous infection by sex showed that the co-infected sub-cohort showed significantly decreased live birth rate, and implantation rate compared with the SARS-CoV-2 -negative cohort. FET with embryos obtained during SARS-CoV-2 infection was negatively associated with pregnant outcomes. Greater efforts are needed to improve clinical interventions and public health policies, based on the negative impact of COVID-19 on human reproductive health.